A Review of Innovative Architectural Façade Strategies for Seismic Design of Tall Buildings - Mouhamad Habib; Ahed Habib; Shimal Younus; Ameen Youns; Ausamah AL Houri; Mahmoud Eissa; Bashar Alibrahim (Journal of Rehabilitation in Civil Engineering)
Designing tall buildings in seismic zones poses significant challenges and requires innovative approaches to ensure structural integrity and aesthetic appeal. Despite the significant advancements in architectural and structural engineering, the literature still lacks a review article that discusses various façade strategies to combine seismic resilience with architectural innovation. This study addresses this gap by reviewing innovative façade technologies and design strategies that enhance the seismic performance of high-rise buildings. Among the discussed façade systems, double-skin façades, when designed as seismic absorbers, can reduce vibrations by 25%. Moreover, the glazed curtain walls can reduce it by 20% to 25%. Other notable systems include masonry building façades, double-skin façades, and multi-hazard resilient façades and approaches that combine multiple mitigation strategies. These findings highlight the importance of integrating seismic performance considerations into façade design and contributes to the development of safer and more resilient tall buildings. The insights offered are valuable for architects, engineers, and urban planners in advancing sustainable and resilient urban environments in earthquake-prone areas.